Academic and journalistic writing in English and Japanese: A contrastive study on stance and engagement expressions - Lee, Nagiko Iwata (Journal of Modern Languages, 2017)
This is a part of the series of English-Japanese contrastive rhetoric research, conducted with the primary focus on the way language is used to express opinions in writing. Following a previous study on newspaper editorials (Lee, 2009), this research involves the examination of 60 research articles from academic journals; 30 articles published in USA and 30 published in Japan. An analysis was made based on Hyland’s (2005) model on stance and engagement in both studies. The results from the two studies are compared to ascertain whether the contrastive characteristics identified are due to the nature of the data, or the linguistic and rhetorical differences between English and Japanese writing. The findings have revealed that the frequent use of ‘questions’ and a paucity of ‘boosters’ in both journalistic and academic writing in Japanese are due to the linguistic and rhetorical characteristics of Japanese writing. In contrast, English journalistic writing is characterized by frequent use of engagement expressions, which was not found in English academic writing. An examination of the ratio of stance and engagement expressions in two different types of data: journalistic and academic, suggests that English writers are more conscious of the genre difference than Japanese writers.